Choosing university leaders in Iraq between appointment and election - a comparative study - Najm, Dr. Sami Hassan (The college of law and political science journal, 2023)
societies developing and building in role acrucial play institutions University to keen are ,role cultivated’universities of importance the to countriesdue,such As.evolution and development its for requirements the all provide and them support adopting on focused is education in interest’ countries ,Accordingly starting ,levels different at leaderships university selecting in methods appropriate and faculty the of dean the through department scientific the of head the from methods the in differ countries ,Therefore .chancellor university the with ending established and long a of countries thedeveloped as ,leaders these selecting of ,leaders university choosing in method election the adopt experience democratic be will this and ,university the of independence the enhances inevitably which have that countries prominent most the ,performance its on positively reflected.Kingdom United the and America of States United the are method this adopted university appointing of method the adopted have countries other,However the by represented authority executive the of dominion exclusive with leaders the Among .bodies teaching the for role any without Education Higher of Ministry Kingdom the and Egypt ,example for ,method applyingthis still are that countries.issue